Can Athletes with Disabilities When Experiencing Anxiety Maximize Performance? - Imaniar, Fitria Putri; Fitri, Mustika; Williyanto, Septian (STKIP PGRI Jombang, 2023)
This study aims to determine the impact of anxiety on the performance of athletes with mild taekwondo disabilities. This type of research is quantitative with a predictive correlation design. The participants in this research were athletes with disabilities in Taekwondo Cahaya Achievement who were members of the Bandung City team to take part in PEPARNAS 2026, West Java Province, totaling 7 people. The instrument used is a questionnaire (CSAI-2) which includes 3 items, namely: cognitive anxiety, somatic anxiety, self-confidence. The research design used predictive correlation analysis and t-test and f-test using the IBM SPSS 26 assistance program. The research results showed that anxiety had no effect on the performance of athletes with disabilities.